Pleomorphic Adenoma of Salivary Glands: an Experience at TUTH - Gurung, U; Shrestha, BL; Sinha, BK; Baskota, DK (Nepalese Journal of ENT Head and Neck Surgery, 2011)
Keywords: pleomorphic adenoma; parotid; submandibular gland; parotidectomy; wide excision DOI: 10.3126/njenthns.v1i1.4729 Nepalese J ENT Head Neck Surg Vol.1 No.1 (2010) p.8-11